Untangling Zebrafish Genetic Annotation: Addressing Complexities and Nomenclature Issues in Orthologous Evaluation of TCOF1 and NOLC1 - Hill-Terán, Guillermina; Petrich, Julieta; Falcone Ferreyra, Maria Lorena; Aybar, Manuel J.; Coux, Gabriela (Journal of molecular evolution, 2024)
Treacher Collins syndrome (TCS) is a genetic disorder affecting facial development, primarily caused by mutations in the TCOF1 gene. TCOF1, along with NOLC1, play important roles in ribosomal RNA transcription and processing. Previously, a zebrafish model of TCS successfully recapitulated the main characteristics of the syndrome by knocking down the expression of a gene on chromosome 13 (coding for Uniprot ID B8JIY2), which was identified as the TCOF1 orthologue. However, database updates renamed this gene as nolc1 and the zebrafish database (ZFIN) identified a different gene on chromosome 14 as the TCOF1 orthologue (coding for Uniprot ID E7F9D9). NOLC1 and TCOF1 are large proteins with unstructured regions and repetitive sequences that complicate alignments and comparisons. Also, the additional whole genome duplication of teleosts sets further difficulty. In this study, we present evidence that endorses that NOLC1 and TCOF1 are paralogs, and that the zebrafish gene on chromosome 14 is a low-complexity LisH domain-containing factor that displays homology to NOLC1 but lacks essential sequence features to accomplish TCOF1 nucleolar functions. Our analysis also supports the idea that zebrafish, as has been suggested for other non-tetrapod vertebrates, lack the TCOF1 gene that is associated with tripartite nucleolus. Using BLAST searches in a group of teleost genomes, we identified fish-specific sequences similar to E7F9D9 zebrafish protein. We propose naming them “LisH-containing Low Complexity Proteins” (LLCP). Interestingly, the gene on chromosome 13 (nolc1 ) displays the sequence features, developmental expression patterns, and phenotypic impact of depletion that are characteristic of TCOF1 functions. These findings suggest that in teleost fish, the nucleolar functions described for both NOLC1 and TCOF1 mediated by their repeated motifs, are carried out by a single gene, nolc1 . Our study, which is mainly based on computational tools available as free web-based algorithms, could help to solve similar conflicts regarding gene orthology in zebrafish.